2011
DOI: 10.1016/j.jinorgbio.2010.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of depleted uranium complexes is independent of p53 activity

Abstract: The p53 tumor suppressor protein is one of the key checkpoints in cellular response to a variety of stress mechanisms, including exposure to various toxic metal complexes. Previous studies have demonstrated that arsenic and chromium complexes are able to activate p53, but there is a dearth of data investigating whether uranium complexes exhibit similar effects. The use of depleted uranium (DU) has increased in recent years, raising concern about DU’s potential carcinogenic effects. Previous studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Our results both support previous reports that uranium exposure leads to DNA damage both in vitro and in human populations, and provides a plausible mechanism for those observations through inhibition of DNA repair proteins. UA alone displayed limited cytotoxicity at levels below 10 μM in keeping with other reports in the literature where cytotoxicity is detected at uranium levels at or greater than 100 μM (Stearns et al, 2005; Periyakaruppan et al, 2007; Thiebault et al, 2007; Milgram et al, 2008; Rouas et al, 2010; Heintze et al, 2011; Orona and Tasat, 2012; Garmash et al, 2014). However, there is evidence that elevated blood uranium levels are associated with increased DNA damage (Popp et al, 2000; Guimaraes et al, 2010; Lourenco et al, 2013) and decreased DNA repair capacity in human populations (Au et al, 1995; Au et al, 1998; Au et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results both support previous reports that uranium exposure leads to DNA damage both in vitro and in human populations, and provides a plausible mechanism for those observations through inhibition of DNA repair proteins. UA alone displayed limited cytotoxicity at levels below 10 μM in keeping with other reports in the literature where cytotoxicity is detected at uranium levels at or greater than 100 μM (Stearns et al, 2005; Periyakaruppan et al, 2007; Thiebault et al, 2007; Milgram et al, 2008; Rouas et al, 2010; Heintze et al, 2011; Orona and Tasat, 2012; Garmash et al, 2014). However, there is evidence that elevated blood uranium levels are associated with increased DNA damage (Popp et al, 2000; Guimaraes et al, 2010; Lourenco et al, 2013) and decreased DNA repair capacity in human populations (Au et al, 1995; Au et al, 1998; Au et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Uranium has been reported to be cytotoxic at high concentrations (>100 μM) in a number of cell lines (Stearns et al, 2005; Coryell and Stearns, 2006; Knobel et al, 2006; Periyakaruppan et al, 2007; Thiebault et al, 2007; Milgram et al, 2008; Periyakaruppan et al, 2009; Darolles et al, 2010; Rouas et al, 2010; Heintze et al, 2011; Orona and Tasat, 2012; Garmash et al, 2014), but there is less published information regarding lower concentrations of uranium. We compared uranyl acetate (UA) toxicity in human embryonic kidney cells (HEK293) and normal human keratinocytes (HEKn).…”
Section: Resultsmentioning
confidence: 99%
“…(45) The comprehensive mechanisms by which DU affects the metabolic functions of the human cells remain to be adequately explored, but many researchers have confidently suggested a cellular and molecular toxicity of DU. (46) Ingestion of food or drinking water contaminated by DU or the inhalation of contaminated air and dust are the most critical pathways of exposure to environmental DU for the general public, whereas direct dermal contact is an insignificant pathway because DU cannot permeate the skin to enter the Table 3: Distribution of congenital anomalies according to the maternal characteristics bloodstream; however, there is a possibility of entry via the exposed injuries. (47) Although there is no considerable proof of hereditary defects resulting from the exposure of parents to DU, studies have indicated that exposure to DU causes a breakdown of DNA strands, which increases with the increasing concentration of radioactive particles left by DU munitions.…”
Section: Depleted Uraniummentioning
confidence: 99%
“…(45) The comprehensive mechanisms by which DU affects the metabolic functions of the human cells remain to be adequately explored, but many researchers have confidently suggested a cellular and molecular toxicity of DU. (46) Ingestion of food or drinking water contaminated by DU or the inhalation of contaminated air and dust are the most critical pathways of exposure to environmental DU for the general public, whereas direct dermal contact is an insignificant pathway because DU cannot permeate the skin to enter the bloodstream; however, there is a possibility of entry via the exposed injuries. (47) Although there is no considerable proof of hereditary defects resulting from the exposure of parents to DU, studies have indicated that exposure to DU causes a breakdown of DNA strands, which increases with the increasing concentration of radioactive particles left by DU munitions.…”
Section: Depleted Uraniummentioning
confidence: 99%